Recent progress in cassava varietal improvement in China - Fang, Baiping; Lin, Xiong; Li, Kaimian; Tian, Yinong (International Center for Tropical Agriculture, 1995)
The paper discusses the research progress mainly for the period of 1990-1993. There are three institutions, SCATC, UCRI and GSCRI, which are systematically working on cassava breeding in China. Since the principal constraint to cassava varietal improvement is the lack of genetic variability, the main approach currently used is the evaluation and selection of hybrid seeds introduced from CIAT/Colombia and from the Thai-CIAT program. In the past few years, remarkable progress has been made in these three institutions, mainly as follows: 1) At SCATC, advanced clones continue to show promising results in comparison with the respectable local control (SC205). Many high-yielding clones were identified in preliminary trials, in which Thai-CIAT material showed a clearly superior performance. 2) At UCRI of the Guangdong Academy of Agric. Sciences, very convincing yield data of a pre-released clone (ZM8002) were obtained from four years of regional trials and another three years of demonstration trials. In addition, many clearly superior new clones were selected from CIAT seed material in a replicated yield trial, nearly doubling the yields of ZM48002 or SC201. Two advanced clones, selected from locally hybridized seeds, showed a high yield potential. 3) At GSCRI, several clones selected from ClAT-introduced seeds showed for the first time a clearly superior yield and dry matter content over local controls in 1992. 4) Additional genetic variability was obtained at SCATC through induced mutations using colchicine treatments. These mutants are presently being evaluated